White matter changes with age utilizing quantitative diffusion MRI - Baker, Laurie M. (Lippincott Williams & Wilkins, 2014)
OBJECTIVE: To investigate the relationship between older age and mean cerebral white matter fiber bundle lengths (FBLs) in specific white matter tracts in the brain using quantified diffusion MRI. METHODS: Sixty-three healthy adults older than 50 years underwent diffusion tensor imaging. Tractography tracings of cerebral white matter fiber bundles were derived from the diffusion tensor imaging data. RESULTS: Results revealed significantly shorter FBLs in the anterior thalamic radiation for every 1-year increase over the age of 50 years. CONCLUSIONS: We investigated the effects of age on FBL in specific white matter tracts in the brains of healthy older individuals utilizing quantified diffusion MRI. The results revealed a significant inverse relationship between age and FBL. Longitudinal studies of FBL across a lifespan are needed to examine the specific changes to the integrity of white matter.